Unified Switching between Active Flying and Perching of a Bioinspired Robot Using Impedance Control - Shanshan Du; Heping Chen; Yong Liu; Runting Hu (Journal of Robotics)
Currently, a bottleneck problem for battery-powered microflying robots is time of endurance. Inspired by flying animal behavior in nature, an innovative mechanism with active flying and perching in the three-dimensional space was proposed to greatly increase mission life and more importantly execute tasks perching on an object in the stationary way. In prior work, we have developed some prototypes of flying and perching robots. However, when the robots switch between flying and perching, it is a challenging issue to deal with the contact between the robot and environment under the traditional position control without considering the stationary obstacle and external force. Therefore, we propose a unified impedance control approach for bioinspired flying and perching robots to smoothly contact with the environment. The dynamic model of the bioinspired robot is deduced, and the proposed impedance control method is employed to control the contact force and displacement with the environment. Simulations including the top perching and side perching and the preliminary experiments were conducted to validate the proposed method. Both simulation and experimental results validate the feasibility of the proposed control methods for controlling a bioinspired flying and perching robot.